Efficiency Optimization Design of L-LLC Resonant Bidirectional DC-DC Converter - Jing Lu; Xiangqian Tong; Jianwu Zeng; Ming Shen; Jun Yin (Energies, 2021)
The new type of L-LLC resonant bidirectional DC-DC converter (L-LLC-BDC) has merits of high efficiency, high-power density and wide gain and power ranges, and it is suitable for energy interface between energy storage systems and DC micro grid. However, the resonances are sensitive to the parasitic parameters, which will deteriorate the efficiency. This paper investigates the intrinsic mechanism of parasitic parameters on the L-LLC-BDC operating principle and working characteristics based on the analysis of working modes and resonance tank. By taking the oscillation of parasitic parameters produced in the stage for the freewheeling stage into consideration, a parameter optimization method is proposed to reduce the resonant current oscillation while maintaining the characteristic of the natural soft switching. The experiment results not only validated the proposed parameter optimization design method, but also testified to the improvement of the efficiency through the minimization of the conduction and switching loss.